Inverted Papilloma of the Middle Ear: Two New Cases and Systematic Review. (October 2022) - Miller, Peter L.; Walsh, Erika; Cho, Do-Yeon; Woodworth, Bradford A.; Grayson, Jessica W.
Introduction: Inverted papillomas of the middle ear are extremely rare tumors that carry an increased risk of recurrence and malignant transformation. There are currently 59 cases of middle ear inverted papillomas reported in the literature. The objective in this study was to systematically evaluate outcomes regarding middle ear inverted papillomas with respect to demographics, anatomical tumor sites, malignant transformation status, recurrence rate and HPV status. Study Design: Retrospective case series and systematic review. Methods: A systematic review was completed on June 25, 2020 with a search strategy including PubMed, Embase, Scopus and Google Scholar. This revealed 181 articles. Full-text review was completed, and 66 articles were included. 115 articles were eliminated due to duplication of articles from databases, article titles not applicable to the aims of the systematic review and articles describing inverted papilloma of body sites other than middle ear. Discussion: Thirty-one cases of primary inverted papillomas of the middle ear were found in the literature with an additional 26 cases of secondary tumors. Four case reports did not specify primary versus secondary. The malignant transformation rate was 34.4% with a 53.6% recurrence rate. Treatment of middle ear inverted papillomas is primarily surgical with adjuvant radiation therapy considered for patients with recurrence or malignant transformation. Frequent clinical follow up of these patients is critical due to the increased rate of recurrence and malignant transformation. Conclusion: Inverted papillomas of the middle ear are rare tumors that carry a high risk of recurrence and malignant transformation necessitating complete resection and frequent clinical follow up.